Comparison of low-density lipoprotein obtained from the Friedewald formula and new formulae in a heterogeneous population - Guevara-Amador, César Augusto; Criollo-Díaz, Claudia Patricia; Pineda-Cañar, Carlos Andrés (Colombia Medica, 2010)
Introduction: Although the levels of low-density lipoprotein (LDL-C) should ideally be determined by beta quantification or enzymatic methods, there are limitations in developing countries. The goal of this study is to compare LDL-C obtained through three formulae (LDL-Cnf) with LDL-C obtained through the Friedewald formula (LDL-Cf) using LDL-C through enzymatic methods as the most-accepted reference method in clinical practice (LDL-Cr).Methods: A concordance study was carried out in a reference laboratory in Cali, Colombia. The three formulae were (mg/dl): Men with triglycerides under 400 mg/dl: LDL-C = Total Cholesterol (TC) - triglycerides (TG) /6.5) - 45; men with triglycerides equal to or greater than 400 mg/dl: LDL-C = (TC - (TG / 7)) -50 and women: LDL-C = (TC-(TG /6.5)) - 70.Results: Three-hundred fifteen values were obtained of which 53% were for women. The mean age and LDL-Cr were 54 years (±15.8) and 112.1 mg/dl (±32.5), respectively. The median (interquartile range, mg/dl) of TC, high-density lipoprotein (HDL-C) and TG were 204 mg/dl (171-229), 51 mg/dl (41-61), and 156 mg/dl (99-237), respectively. There were no differences between mean values of LDL-Cr and LDL-Cnf (113.48 vs. 112.67 mg/dl; p=0.45). The intraclass correlation coefficient among LDL-Cr and LDL-Cf and LDL-Cnf were high (R=0.93 and 0.92, respectively). The correlation between LDL-Cf and LDL-Cnf was 0.95. There is no difference between the areas under the receiver operating characteristic (ROC) curve with the level of LDL-Cr at 160 mg/dl for LDL-Cnf and LDL-Cf. (0.94 vs. 0.93; p=0.27).Conclusion: There is high concordance between LDL-Cf and LDL-Cnf. These formulae could be an alternative when there are limitations to determine LDL-C because of the lack of enzymatic methods or through Friedewald formula due to the absence of HDL-C.